1998
DOI: 10.1046/j.1365-3016.12.s2.6.x
|View full text |Cite
|
Sign up to set email alerts
|

Who should provide routine antenatal care for low‐risk women, and how often? A systematic review of randomised controlled trials

Abstract: Summary. Many activities, the timing and the frequency of visits of conventional antenatal care provided to low-risk pregnant women have most often been introduced without proper scientific evaluation. Few trials, to date, have been conducted to evaluate the effectiveness of antenatal care programmes for low-risk women with varied number of antenatal visits and type of care providers. We have performed a systematic review of these randomised controlled trials.Five randomised controlled trials were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 20 publications
3
31
0
4
Order By: Relevance
“…However, there were no differences between the two models regarding neonatal results. Other authors likewise found no significant statistical differences regarding maternal or neonatal morbidity with simply increasing the number of visits [13][14][15].…”
Section: Introductionmentioning
confidence: 90%
“…However, there were no differences between the two models regarding neonatal results. Other authors likewise found no significant statistical differences regarding maternal or neonatal morbidity with simply increasing the number of visits [13][14][15].…”
Section: Introductionmentioning
confidence: 90%
“…O pré-natal foi avaliado de duas formas: um critério de utilização, elaborado por Kotelchuck 13 15,16,17,18,19 . Para este critério, a realização dos procedimentos considerados efetivos no pré-natal foi tão importante quanto o número de consultas.…”
Section: Metodologiaunclassified
“…Such care includes early detection and better management of maternal pre-pregnancy or pregnancy-induced medical disorders such as hypertension, diabetes, Rh-isoimmunization, and IUGR. Yet, the effectiveness of antenatal care in reducing fetai mortality among women at low risk is unc1ear (Grant et al, 1989;Khan-Neelofur D, 1998 To date, the largest randomized controlled trial of routine ultrasound screening to be reported, the Routine Antenatal Diagnostic Ultrasound Study (RADUS) invoiving 15,151 pregnant women at low-risk for perinatal problems in 6 U.S. states showed no benefit.…”
Section: Temporal Trendsmentioning
confidence: 99%